Modernism between History and Academia - Mihálycsa, Erika (Hungarian Journal of English and American Studies, 2021)
Books reviewed:Bahun, Sanja. Modernism and Melancholia: Writing as Countermourning. Oxford: OUP, 2014. 236 pages. ISBN 978-0-19-997795-6. Hb. $45.00.Goldstone, Andrew. Fictions of Autonomy: Modernism from Wilde to de Man. Oxford: OUP, 2013. 204 pages. ISBN 978-0-19-986112-5. Hb. $73.00.